How can the security of international trade be financed in developing countries? A global public good approach - Dulbecco, Philippe (2005)
Identifies the modalities of financing international trade security. Focuses on the issue of financing developing countries, which must make a considerable effort to attain the required level, whereas the developed countries have already invested heavily in trade security since the events of September 11, 2001.